(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
A three years old Holstein Friesian (HF) cow with a history of premature calving was brought to the clinics of Veterinary college and Research Institute, Nammakal. The cow showed protrusion of mass through the vulva after its first calving. On clinical examination animal was apparently healthy and confirmed as uterine prolapse. The Uterine prolapse was corrected manually following proper precautionary measures. To prevent the recurrence, Buhner’s suture was applied. Animal had an uneventful recovery. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 251-254